Agricultural Terms of Trade in Pakistan - Khan, Abdul Aleem; Hyder, Kalim (JISR management and social sciences & economics, 2005)
The government in Pakistan is designing new policies to cope up with the requirements of free trade regime. Agriculture apart from being the largest sector is also one of the most affected sectors of the economy. Changes in the tariffs and subsidies structure have largely affected the domestic input and output prices and the consumer prices. The question now is that whether the prospects for the people depending on crop income have improved in terms of profitability and standard of living or not?